Elephant-induced damage drives spatial isolation of the dioecious palm Borassus aethiopum (Arecaceae) in the Pendjari National Park, Benin. - SALAKO, Valère; Azihou, Akomian Fortuné.; ASSOGBADJO, ACHILLE EPHREM; Houéhanou, Thierry D.; Kassa, Barthelemy; Glèlè, Romain L. (My University, 2015)
Spatial patterns (SP) of treefall by elephants is known to be clustered across landscapes as a result of food selection and group foraging. Yet, few studies have explicitly elucidated how elephant pressure (EP) alters SP and tree-to-tree distance of tree species especially for dioecious plant species, at stand scale. Using the pair-correlation function and distance to the nearest neighbour on spatial data from ﬁve plots of 1–1.5 ha, this article compared SP of damaged and undamaged individuals and tree-to-tree distance of the dioecious palm Borassus aethiopum Mart. in stands of low versus high EP in the Pendjari National Park. We tested the hypothesis that high EP would modify SP and results into isolated adults. Nested ANOVAs were used to compare distances. The overall SP of individuals did not vary, but distance among living adults was twofold extended in stands of high EP. The Janzen–Connell escape hypothesis is supported by our data for ungrazed saplings. The study concluded that increasing EP reduces density and induces spatial isolation of adults that may increase pollination failure and threat persistence of B. aethiopum.
Keywords: Benin; Borassus aethiopum Mart.; damages; Loxodonta africana Blumenbach; pair-correlation function; spatial pattern